Renewable-powered hydrogen economy from Australia's perspective. (21st September 2020) - Milani, Dia; Kiani, Ali; McNaughton, Robbie
Abstract: This article broadly reviews the state-of-the-art technologies for hydrogen production routes, and methods of renewable integration. It outlines the main techno-economic enabler factors for Australia to transform and lead the regional energy market. Two main categories for competitive and commercial-scale hydrogen production routes in Australia are identified: 1) electrolysis powered by renewable, and 2) fossil fuel cracking via steam methane reforming (SMR) or coal gasification which must be coupled with carbon capture and sequestration (CCS). It is reported that Australia is able to competitively lower the levelized cost of hydrogen (LCOH) to a record (1.88–2.30)/kgH2 for SMR technologies, and (2.02–2.47)/kgH2 for black-coal gasification technologies. Comparatively, the LCOH via electrolysis technologies is in the range of (4.78–5.84)/kgH2 for the alkaline electrolysis (AE) and (6.08–7.43)/kgH2 for the proton exchange membrane (PEM) counterparts. Nevertheless, hydrogen production must be linked to the right infrastructure in transport-storage-conversion to demonstrate appealing business models. Graphical abstract: Image 1 Highlights: The role of hydrogen as a mean of future sustainable energy carrier is recognized. Renewable integration routes in hydrogen production technologies are categorized. The key drivers for commercial-scale hydrogen production in Australia are identified. Fossil fuel cracking coupled with CCS is the most viable hydrogen production route. Electrolysis coupled with renewable is costly and would require more R&D to contest.